Optimization of yellow passion fruit peel extraction method using methanol solvent to increase antioxidant activity - Khoirul Ngibad; Muhammad Sungging Pradana; Juli Afifah; Aulia Afiatunnisa (Jurnal Pijar Mipa, 2023)
This study aims to determine the concentration of methanol solvent, the temperature, and the time of the shaker in the best extraction. It can produce the best antioxidant activity of the peel of the yellow passion fruit (Passiflora edulis Sims f. flavicarpa Deg) using the DPPH method. The maceration process is carried out using methanol solvents. The filtrate is concentrated with a rotary evaporator until a concentrated extract is obtained. Variations in methanol concentrations include 60, 80, and 100% (v/v) in methanol-water solvent mixtures. Shaker time variations in the extraction process include: 120, 140, and 160 minutes and shaker temperature variations in the extraction process include: 55, 65, and 75 °C. The results showed that the concentration of methanol solvent that can produce the best antioxidant activity from the peel of yellow passion fruit using the DPPH method is a concentration of 100% with an IC50 value of 31 ppm, followed by methanol solvents of 60% and 80% which produce IC50 values of 35 and 41 ppm, respectively. The optimum shaker time in the extraction process is 140 minutes, and the optimum shaker temperature in the extraction process is 65 oC. The conclusion is that using 100% methanol solvent, 140 minutes shaker time, and 65 oC shaker temperature can increase antioxidant activity in vitro using the DPPH method.